“Elaboracion de macerados regionales de uva borgoña negra (vitis lubrasca), indano (byrsonima crassifolia L.Rich.) y huiyo ( genipa americana L.) usando aguardiente de caña y endulsantes miel de caña de azucar y azucar invertido - Macedo Pérez, Wiler (2008)
This research is aimed at developing regional macerated; Burgundy grape black (vitis labrusca), The lndano (Byrsonima crassifolia L. Rich), And Huito (Genipa americana L.); Maceration using as a solution to the sugar cane liquor and two types of sweeteners: Honey sugarcane and invert sugar; also was tested and compared clarified using gelatin and Bentonite in the macerated obtained. During the maceration time (90 days) was assessed using the power dulzaíno same concentration of sweeteners (70º Brix), compared with the same strength of spirit (42º GL), as determined by the physicochemical characteristics (%SS, PH, acidity, density and alcoholic strength). Was submitted after maceration to the test of clarification with Gelatin (0.50 g / lt) and Bentonite (0.80 g / lt). Whose results were evaluated by sensory analysis (test affective) and the differences between the treatments for proof Duncan and ANV A 5% significance. The final flowchart used for the development of regional macerated was: Grape, black variety Burgundy (SS = 15.0% ), and picking off selected, heavy, disinfected and washed, drained; Maceration 1 (sugar cane brandy for 10-15 days at 42º GL), Maceration 2 (Sweetener: invert sugar to 70 degrees Brix, for 75-80 days), physico-chemical evaluation, clarification: Gelatin 0.50 g / lt. (From the third month for 15 days), filtration, and evaluated product packaging, storage. Huito (SS% = 14.1); cleaned, cut and elirnination of seeds, heavy, disinfected and washed, drained: Maceration 1 (Brandy 42º GL for 10-15 days), Maceration 2 (Sweetener: honey cane at 70 degrees Brix, for 75-80 days) Evaluation physico-chemical clarification: Bentonite 0.80 g / lt. (For 15 days beginning of the third month), filtration, and evaluated product packaging, storage. Indano (SS = 4.1 %), cleaning and sorting, weighing, washing drained and disinfected; Maceration 1 (Brandy for 10-15 days), Maceration 2 (Sweetener: honey cane than 70 degrees Brix, for 75-80 days ), Evaluation physical-chemical Clarification: Gelatin 0.50 g / lt. (For 15 days beginning of the third month), filtration, and evaluated product packaging, storage. After maceration time, we obtained the following parameters: Macerado Grape: soluble solids (%) 20.4, density (g / ml) 1028, acidity (%) 0201,pH 4.64, alcoholic strength (ºS) 25.Macerado of Huito: soluble solids (%) 21.6, density (g / ml) 1029, acidity (%) 0416,pH 4.48, alcoholic strength (ºS) 26.1. Macerado of Indano: soluble solids (%) 21.5, density (g / ml) 1028, acidity (%) 0298, pH 4.68, alcoholic strength (ºS) 25.8 No significant changes were noted in the color or flavor, so they were stored in a cool and safe at room temperature.